2019
DOI: 10.1080/21645515.2019.1680084
|View full text |Cite
|
Sign up to set email alerts
|

The impact of meningococcal conjugate vaccine (MenACWY-TT) on meningococcal carriage in Hajj Pilgrims returning to Turkey

Abstract: Meningococcal conjugate vaccine was administered for the first time to pilgrims in 2018 in Turkey prior to their departure to the Hajj. This study aimed to determine the effect of vaccination on the prevalence of Neisseria meningitidis carriage among the pilgrims returning to Turkey. This prospective paired (departing and arriving) cohort study included pilgrims aged 10-80 years and compared N.meningitidis carriage before and after pilgrimage. Oropharyngeal samples were collected from 229 pilgrims before depar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 16 publications
(21 reference statements)
0
15
0
Order By: Relevance
“…All: 27.4 - A: 0.3 - B: 1.7 - W135: 25.0 - Y: 0.3 III. Household contacts post Hajj 2010: 25.6 Children and adults (NR): 25.6 All: 25.6 W135: 25.6 Adults (20–70 y): 2.5 Turkey [ 122 ] Cohort study Esenboğa Airport (Ankara) Pilgrims N = 229 (pre-Hajj, paired cohort) N = 229 (post-Hajj, paired cohort) Hajj study I. Pre-Hajj 2018: 3.9 I. Children and adults (10–80 y): 3.9 I.…”
Section: Objective 1: Asymptomatic Meningococcal Carriagementioning
confidence: 99%
See 1 more Smart Citation
“…All: 27.4 - A: 0.3 - B: 1.7 - W135: 25.0 - Y: 0.3 III. Household contacts post Hajj 2010: 25.6 Children and adults (NR): 25.6 All: 25.6 W135: 25.6 Adults (20–70 y): 2.5 Turkey [ 122 ] Cohort study Esenboğa Airport (Ankara) Pilgrims N = 229 (pre-Hajj, paired cohort) N = 229 (post-Hajj, paired cohort) Hajj study I. Pre-Hajj 2018: 3.9 I. Children and adults (10–80 y): 3.9 I.…”
Section: Objective 1: Asymptomatic Meningococcal Carriagementioning
confidence: 99%
“…household contacts, military personnel, pilgrims or students), the most extensive data were available in the pilgrim population (Table 1 ). Data were available from Iran (n = 6) [ 33 – 38 ], Kuwait (n = 1) [ 39 ], Saudi Arabia (n = 6) [ 40 – 45 ], and Turkey (n = 3) [ 46 – 48 ]. Asymptomatic carriage rates ranged from 4.2% (Turkey) [ 46 ] to 32.9% (Iran) [ 35 ] in the military risk group (n = 3 studies), from 0.0% (Iran [ 36 ], Kuwait [ 39 ]) to 27.4% (Turkey [ 47 ]) in the pilgrim risk group (n = 11 studies) and from 6.9 to 12.3% (both Iran [ 37 , 38 ]) in the student risk group (n = 2 studies).…”
Section: Objective 1: Asymptomatic Meningococcal Carriagementioning
confidence: 99%
“…For the 2018 Hajj, of 229 Hajj pilgrims aged 10-80 years (all of whom had received conjugated MenACWY vaccine at least 2 weeks prior to sampling), carriage was identified in 3.9% immediately prior to departure (all of which were MenB). Following their return, although overall carriage rates were not reported, paired sampling found MenB acquisition in 1/229 (0.4%) of returning pilgrims [89].…”
Section: Carriagementioning
confidence: 91%
“…MenW (66.6%) was the most prevalent serogroup, with 9.4% of isolates due to MenB [87]. Data for carriage in Turkish pilgrims are available for both the 2010 and 2018 Hajj [88,89]. In 2010, carriage was identified in 13.3% of pilgrims prior to departure, the majority being MenW (82.5%) followed by MenB (14.3%).…”
Section: Carriagementioning
confidence: 99%
“…Since then, vaccination of participants has been carried out. 16,17 At the 23rd World Scout Jamboree (WSJ2015) held in Japan in 2015, it was reported that three Scouts from the North Scotland Corps and one Scout from the Swedish Corps developed meningococcal infection. 18,19 In addition, epidemics of infectious diseases such as influenza, measles, and norovirus 20 have been reported at mass gathering events.…”
Section: Risks and Benefits Of Mass Gathering Events For The Local Health-care Systemmentioning
confidence: 99%